Insights into the Evolutionary History of an Extinct South American Freshwater Snail based on Historical DNA - Vogler, Roberto Eugenio (2016)
Highly oxygenated freshwater habitats in the High Paraná River (Argentina–Paraguay) were home to highly endemic snails of the genus Aylacostoma, which face extinction owing to the impoundment of the Yacyretá Reservoir in the 1990s. Two species, A. chloroticum and A. brunneum, are currently included in an ongoing ex situ conservation programme, whereas A. guaraniticum and A. stigmaticum are presumed extinct. Consequently, the validity and affinities of the latter two have remained enigmatic. Here, we provide the first molecular data on the extinct A. stigmaticum by means of historical DNA analysis. We describe patterns of molecular evolution based on partial sequences of the mitochondrial 12S ribosomal RNA gene from the extinct species and from those being bred within the ex situ programme. We further use this gene to derive a secondary structure model, to examine the specific status of A. stigmaticum and to explore the evolutionary history of these snails. The secondary structure model based on A. stigmaticum revealed that most polymorphic sites are located in unpaired regions. Our results support the view that the mitochondrial 12S region is an efficient marker for the discrimination of species, and the extinct A. stigmaticum is recognized here as a distinct evolutionary genetic species. Molecular phylogenetic analyses revealed a sister group relationship between A. chloroticum and A. brunneum, and estimated divergence times suggest that diversification of Aylacostoma in the High Paraná River might have started in the late Miocene via intra-basin speciation due to a past marine transgression. Finally, our findings reveal that DNA may be obtained from dried specimens at least 80 years after their collection, and confirms the feasibility of extracting historical DNA from museum collections for elucidating evolutionary patterns and processes in gastropods.